2016
DOI: 10.4103/1119-3077.173716
|View full text |Cite
|
Sign up to set email alerts
|

Medication education program for Indian children with asthma: A feasibility stud

Abstract: An asthma educator delivered interactive program simultaneously involving children with asthma and their parents, improved quality of life, empowered and promoted better self-management skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 35 publications
1
37
0
11
Order By: Relevance
“…We identified eight studies where the inhaler training interventions (including such aspects as physical demonstration, technique labels, and written action plans) led to an improvement in inhaler technique and also a significant increase in disease control, (seven in asthma [ 39 , 83 , 84 , 87 , 94 , 96 , 111 ], and one in COPD [ 88 ]) while 4 studies reported that their intervention significantly improved disease outcomes or reduced hospital admission frequency, but did not measure inhaler error frequency [ 98 , 105 , 116 , 117 ]. Two further studies reported that training significantly improved technique and outcomes in asthma, but not in COPD patients [ 68 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified eight studies where the inhaler training interventions (including such aspects as physical demonstration, technique labels, and written action plans) led to an improvement in inhaler technique and also a significant increase in disease control, (seven in asthma [ 39 , 83 , 84 , 87 , 94 , 96 , 111 ], and one in COPD [ 88 ]) while 4 studies reported that their intervention significantly improved disease outcomes or reduced hospital admission frequency, but did not measure inhaler error frequency [ 98 , 105 , 116 , 117 ]. Two further studies reported that training significantly improved technique and outcomes in asthma, but not in COPD patients [ 68 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were multi-centre (Moudgil 2000;Valery 2010) and five were single-centre studies (Blixen 2001;La Roche 2006;Canino 2008;Poureslami 2012;Grover 2016). Two studies (Blixen 2001; Poureslami 2012) examined adults and four studies examined children (La Roche 2006;Canino 2008;Valery 2010;Grover 2016). The study by (Moudgil 2000) included both adults and children, however specific results for adults and children were not presented in the published paper.…”
Section: Included Studiesmentioning
confidence: 99%
“…Three studies (La Roche 2006;Canino 2008;Grover 2016) were assessed as low risk, as > 90% of participants were followed up. Three studies (Moudgil 2000;Poureslami 2012;Valery 2010) were assessed as an unclear risk.…”
Section: Incomplete Outcome Datamentioning
confidence: 99%
“…In recent years, several research groups have implemented culturally tailored interventions, with or without participatory design, A systematic review of culture-specific programmes for adults and children with asthma [ 38 ] found four relevant randomised controlled trials (RCTs) in 2009, and an additional three RCTs in a 2017 update (a total of seven), of which three involved South Asians (two in high-income countries) [ 39 41 ]. All seven RCTs provided individual and/or group-setting educational classes and support groups or materials for asthma management, while the control groups received either no intervention or partial intervention (e.g.…”
Section: Introductionmentioning
confidence: 99%